METRICS AND INDICATORS IN ADAPTATION PROCESS OF EMPLOYEES AT SOCIAL ENTERPRISES - Yurchenko, Halyna (Sworld-Us Conference proceedings, 2023)
The theoretical aspects of the concept of a social enterprise were considered, and the algorithm for the implementation of modeling processes of adaptation of employees of social enterprises was defined. Different definitions of social enterprise and its